Levantamento soroepidemiológico e isolamento do Toxoplasma gondii em galinhas caipiras (Gallus gallus domesticus) no Estado do Espírito Santo, Brasil - Beltrame, Marcus Alexandre Vaillant (2010)
Introduction. The prevalence of Toxoplasma gondii infection in free-range chickens varies in different regions and we do not know the prevalence of this infection in free-range chickens in the state of Espirito Santo. Objective. To study the prevalence of infection by T. gondii in free-range chickens from different municipalities of the E. Santo, to try the isolation of the parasite from tissues of positive chickens and to search the knowledge on the parasite and the disease it produces among people living in the rural properties from which the samples were collected. Methods. Detection of anti-T. gondii in the serum of 510 chickens from rural areas of eight municipalities of E. Santo, using indirect hemagglutination (IHA) and modified agglutination test (MAT). Bioassay was conducted in mice by intra-peritoneal injection of macerated of thigh muscle, brain and heart from 64 positive chickens. Questionnaires were used to assess environmental conditions related to the protozoan in each farm and the knowledge of people on the parasite. Results. Anti-T. gondii antibodies were detected in 40.4% (95% CI: 36.1 to 44.7) by IHA and 38.8% (95% CI: 34.6 to 43) by MAT. Among the 64 chickens submitted to bioassay, the parasite was isolated from 48 (75%, 95% CI: 85.6 to 64.4), with mortality occurring from 10 through 31days after infection, and in two chickens presented seroconversion. Conclusions. (a) A high prevalence of anti-T. gondii antibodies with high frequency of parasite isolation from positive chickens, was observed in free range chickens in E. Santo;(b) The high mortality observed in mice used in the bioassay may be in relationship with the virulence of isolated strains; (c) There was good concordance (82%) between IHA and MAT, therefore IHA may indicated as a screening test for anti-T. gondii antibodies in chickens; (d) presence of cats in promiscuity with birds and other species occurred in 73% of the properties and (e) The questionnaire revealed ignorance of the people living in the visited farms about the protozoan, the disease it produces and its transmission mechanisms.